General Anesthesia and Cerebral Function: Changes in Cognition and Regional Brain Metabolism in Patients following Surgery. (20th December 2022) - Struble, Helen; Liu, Stephen; Silverman, Daniel H
Abstract: Background: Improved understanding of relationships between general anesthesia and subsequent cognitive decline is critically needed. In this study, previously healthy and mildly impaired subjects were compared pre‐ and post‐surgery, with respect to longitudinal assessments of their neuropsychologic performance and regional brain metabolism. Method: We screened records of 1, 450 Alzheimer's Disease Neuroimaging Initiative subjects to identify all those undergoing non‐cancer surgeries involving general anesthesia with a minimum of two pre‐surgical and two post‐surgical ADNI visits, yielding neuropsychological data for this analysis acquired during 256 visits by 64 subjects – 32 surgical patients meeting the above criteria, and 32 controls who were demographically matched but with no reported surgeries during enrollment. Cognitive domain scores were correlated with rates of decline in regional cerebral metabolism based on interval changes in pairs of FDG‐PET scans acquired pre‐ and post‐surgery; analogous calculations were performed in the non‐surgical group by setting "surgery" dates according to median elapsed time from first visit to surgery in the surgical group. Imaging data were quantitatively examined by both standardized volume of interest (sVOI) and statistical parametric mapping (spm) methods of analysis. Result: sVOIs included bilaterally 6 frontal, 5 temporal, 4 parietal, 2 occipital, and sensorimotor cerebral cortical volumes, as well as 7 noncortical volumes. Compared to the non‐surgical group, the surgical group showed greater post‐surgical decline in the two anterior temporal volumes measured (p=0.01), both medially (including the hippocampus and adjacent cortex) and laterally. Within the surgery group, comparing pre‐ versus post‐ timeframes also identified most significant accelerated decline in the two anterior temporal volumes. The spm analyses corroborated significant acceleration of metabolic decline postsurgically in temporal cortex, predominantly in the right hemisphere, with cluster size significant after statistical adjustment for multiple comparisons (P<0.0005, Pcorr = 0.047). Finally, pre‐ and post‐surgical differences in rates of temporal metabolic decline correlated with differences in executive function decline within the surgical group (r=0.785). Conclusion: Major surgeries involving general anesthesia were associated with significantly accelerated decline in temporal metabolism postsurgically. This in turn was correlated with greater acceleration of decline in cognitive function of surgical patients.